Trends and Predictors of Cigarette Smoking Among HIV Seropositive and Seronegative Men: The Multicenter AIDS Cohort Study - Akhtar-Khaleel, Wajiha Z (AIDS Behav, 2016)
We measured the trend of cigarette smoking among HIV-seropositive and seronegative men over time from 1984-2012. Additionally, we examined the demographic correlates of smoking and smoking consumption. 6,577 men who have sex with men (MSM) from the Multicenter AIDS Cohort Study (MACS) were asked detailed information about their smoking history since their visit. Prevalence of smoking and quantity smoked was calculated yearly from 1984-2012. Poisson regression with robust error variance was used to estimate prevalence ratios of smoking in univariate and multivariate models. In 2012, 11.8% and 36.9% of men who were enrolled in the MACS before 2001 or during or after 2001 smoked cigarettes, respectively. In the multivariate analysis, black, non-Hispanic, lower education, enrollment wave, alcohol use, and marijuana use were positively associated with current smoking in MSM. HIV serostatus was not significant in the multivariate analysis. However, HIV variables, such as detectable viral load, were positively associated. Though cigarette smoking has declined over time, the prevalence still remains high among subgroups. There is still a need for tailored smoking cessation programs to decrease the risk of smoking in HIV-seropositive men who have sex with men.